2011
DOI: 10.1016/j.jtbi.2010.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Food web framework for size-structured populations

Abstract: We synthesise traditional unstructured food webs, allometric body size scaling, trait-based modelling, and physiologically structured modelling to provide a novel and ecologically relevant tool for size-structured food webs. The framework allows food web models to include ontogenetic growth and life-history omnivory at the individual level by resolving the population structure of each species as a size-spectrum. Each species is characterised by the trait 'size at maturation', and all model parameters are made … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
351
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 189 publications
(360 citation statements)
references
References 66 publications
8
351
0
1
Order By: Relevance
“…After each set of invasions, species that go extinct are removed. This method of gradually building up a foodweb resolves the marine foodweb modelling problem first described by Andersen and Ursin (1977): without sufficiently strong non-trophic intraspecific competition, empirically parametrized foodweb models with many species tend to be dynamically unstable (Andersen and Ursin, 1977;Loeuille and Loreau, 2005;Andersen and Pedersen, 2010;Hartvig et al, 2011). The PDMM assembly algorithm produces stable communities with inter-and intraspecific competition between consumers resulting only from trophic mechanisms that are well understood, namely resource-and consumer-mediated competition.…”
Section: The Population-dynamical Matching Modelmentioning
confidence: 95%
See 4 more Smart Citations
“…After each set of invasions, species that go extinct are removed. This method of gradually building up a foodweb resolves the marine foodweb modelling problem first described by Andersen and Ursin (1977): without sufficiently strong non-trophic intraspecific competition, empirically parametrized foodweb models with many species tend to be dynamically unstable (Andersen and Ursin, 1977;Loeuille and Loreau, 2005;Andersen and Pedersen, 2010;Hartvig et al, 2011). The PDMM assembly algorithm produces stable communities with inter-and intraspecific competition between consumers resulting only from trophic mechanisms that are well understood, namely resource-and consumer-mediated competition.…”
Section: The Population-dynamical Matching Modelmentioning
confidence: 95%
“…The first, the population-dynamical matching model (PDMM) of Rossberg et al (2008), was used to determine whether the observed relations between the LFI and the LSI relied on ecological mechanisms specific to the Celtic Sea fish community or on more general mechanisms that could be shared with other fish communities. The second, the fish community size-resolved model (FCSRM) of Hartvig et al (2011), was used to understand the observed intraspecific size structures and their responses to size-selective fishing, using generic model assumptions.…”
Section: Modellingmentioning
confidence: 99%
See 3 more Smart Citations